Avaliação de riscos com simulação de Monte Carlo em obras de grande porte - Cavalcante Filho, João Umberto de Paula (2019)
Civil construction is one of the most dynamic, risky and challenging. As a result, the industry presented many management problems, presenting a high rate of projects with failures, mainly in their deadlines and budgets. Risk Management (RG) comes up to improve the efficiency of projects in the sector. This work presents a model of risk assessment in large projects, able to calculate the project time, identify and evaluate the risks in occurrence and impact. Data have been collected from the main stages of execution of a large work in the city of Fortaleza / CE, with three engineers specialized in large projects, the first one was used for modeling the simulation, the others were used for the scenario analysis of the case. All information gathered were used as input data to the software @ risk for a Monte Carlo Simulation (MCS). The simulation brings the possibility to obtain the cost budget and schedule for an 80% confidence interval, as well as an inscription of the risks that cause the extrapolation of the budget and delays. Among the main factors, it cites the factors incident to the financial, managerial and project risks, such as the delay in receiving the payments, the inadequate planning and the differences found in the site of the project, they were the most impact factors. Contingency reserves for the budget and schedule have been found: related to costs of 11.60% and 11.91% for scenarios 1 and 2. Regarding the schedule, the values were much higher, being: 72.50% and 59.68%. The model proved effective in: identification of risks in large scale projects; estimates of costs and time; calculate contingency reserve values for project risks; submit a tool for statistical analysis of decision making for contractors and contractors; provide needed information to move forward with the risk management.